Problematika Internalisasi Pendidikan Karakter di Indonesia - Purwandi, Ayi Dini (Tsamratul Fikri | Jurnal Studi Islam, 2019)
The purpose of this study is to analyze the problems of internalizing character education in Indonesia using several methods, including meta-analysis. the way to formulate the problem of this research begins with conducting observations, then tracing the results of other relevant research to be analyzed. The research data consisted of six journal articles and four theses that had been tried. The process of data analysis is done by descriptive qualitative method. The results of the analysis show that there is a problem in internalizing character education in Indonesia because the current problem of internalizing character education is (a) students' lack of interest in practicing the nation's character and culture (b) The internalisation system of character values ​​in schools is not continued by the environment outside the school (c) Crisis exemplary ( d) Foreign culture that is not in accordance with the culture and character of the Indonesian nation is entered into a large scale (e) Learning programs that are less relevant to the times. The expected solution to the internalization of character education is (a) conceptual approach (b) systematic / habituation approach (c) modeling / exemplary approach. The educational model for character development in adolescents is integrated in school regulations, learning and extracurricular activities, namely scout extracurricular activities. Based on the results of the analysis it can be concluded that an effective character education model is built from a school climate that is conducive to the development of positive character both through learning models at school.